Effects of spin–orbit coupling and many-body correlations in STM transport through copper phthalocyanine - Siegert, Benjamin; Donarini, Andrea; Grifoni, Milena (Beilstein Journal of Nanotechnology, 2015)
The interplay of exchange correlations and spin–orbit interaction (SOI) on the many-body spectrum of a copper phtalocyanine (CuPc) molecule and their signatures in transport are investigated. We first derive a minimal model Hamiltonian in a basis of frontier orbitals that is able to reproduce experimentally observed singlet–triplet splittings. In a second step SOI effects are included perturbatively. Major consequences of the SOI are the splitting of former degenerate levels and a magnetic anisotropy, which can be captured by an effective low-energy spin Hamiltonian. We show that scanning tunneling microscopy-based magnetoconductance measurements can yield clear signatures of both these SOI-induced effects.
Keywords: anisotropy; copper phthalocyanine; magnetotransport; spin–orbit interaction; scanning tunneling microscopy (STM)

Molecular Nanomagnets - Gatteschi, D.; Sessoli, R.; Villain, J. (Oxford University Press, 2006)

Electron Paramagnetic Resonance of Transition Ions - Abragam, A.; Bleaney, B. (Oxford University Press, 1970)

(untitled) - Mannini, M.; Pineider, F.; Danieli, C.; Totti, F.; Sorace, L.; Sainctavit, P.; Arrio, M.-A.; Otero, E.; Joly, L.; Cezar, J. C.; Cornia, A.; Sessoli, R. (Nature, 2010)

(untitled) - Chiesa, A.; Carretta, S.; Santini, P.; Amoretti, G.; Pavarini, E. (Phys. Rev. Lett., 2013)

(untitled) - Misiorny, M.; Burzurí, E.; Gaudenzi, R.; Park, K.; Leijnse, M.; Wegewijs, M. R.; Paaske, J.; Cornia, A.; van der Zant, H. S. J. (Phys. Rev. B, 2015)

(untitled) - Burzurí, E.; Gaudenzi, R.; van der Zant, H. S. J. (J. Phys.: Condens. Matter, 2015)

(untitled) - Liao, M.-S.; Scheiner, S. (J. Chem. Phys., 2001)

(untitled) - Mugarza, A.; Robles, R.; Krull, C.; Korytár, R.; Lorente, N.; Gambardella, P. (Phys. Rev. B, 2012)

(untitled) - Stepanow, S.; Mugarza, A.; Ceballos, G.; Moras, P.; Cezar, J. C.; Carbone, C.; Gambardella, P. (Phys. Rev. B, 2010)

(untitled) - Schulz, F.; Ijäs, M.; Drost, R.; Hämäläinen, S. K.; Harju, A.; Seitsonen, A. P.; Liljeroth, P. (Nat. Phys., 2015)

(untitled) - Siegert, B.; Donarini, A.; Grifoni, M. (arXiv, 2015)

(untitled) - Ryndyk, D. A.; Donarini, A.; Grifoni, M.; Richter, K. (Phys. Rev. B, 2013)

(untitled) - Repp, J.; Meyer, G.; Stojković, S. M.; Gourdon, A.; Joachim, C. (Phys. Rev. Lett., 2005)

(untitled) - Swart, I.; Sonnleitner, T.; Repp, J. (Nano Lett., 2011)

Atomic Structure Calculations I. Hartree-Fock Energy Results for the Elements Hydrogen to Lawrencium - Mann, J. B. (Los Alamos Scientific Laboratory of the University of California, 1967)

(untitled) - Slater, J. C.; Koster, G. F. (Phys. Rev., 1954)

(untitled) - Froyen, S.; Harrison, W. A. (Phys. Rev. B, 1979)

(untitled) - Siegert, B.; Donarini, A.; Grifoni, M. (Phys. Status Solidi B, 2013)

GNU Scientific Library Reference Manual - Galassi, M.; Davies, J.; Theiler, J.; Gough, B.; Jungman, G.; Alken, P.; Booth, M.; Rossi, F. (Network Theory Limited, 2009)

(untitled) - Bendix, J.; Brorson, M.; Schaffer, C. E. (Inorg. Chem., 1993)

(untitled) - Yu, Z. G. (Phys. Rev. B, 2012)

(untitled) - Dzyaloshinsky, I. (J. Phys. Chem. Solids, 1958)

(untitled) - Moriya, T. (Phys. Rev. Lett., 1960)

(untitled) - Miyahara, S.; Fouet, J.-B.; Manmana, S. R.; Noack, R. M.; Mayaffre, H.; Sheikin, I.; Berthier, C.; Mila, F. (Phys. Rev. B, 2007)

(untitled) - Herzog, S.; Wegewijs, M. R. (Nanotechnology, 2010)

(untitled) - Sobczyk, S.; Donarini, A.; Grifoni, M. (Phys. Rev. B, 2012)

(untitled) - Donarini, A.; Siegert, B.; Sobczyk, S.; Grifoni, M. (Phys. Rev. B, 2012)

(untitled) - Kaasbjerg, K.; Flensberg, K. (Phys. Rev. B, 2011)

(untitled) - Darau, D.; Begemann, G.; Donarini, A.; Grifoni, M. (Phys. Rev. B, 2009)

(untitled) - Koch, J.; von Oppen, F. (Phys. Rev. Lett., 2005)

(untitled) - Laird, E. A.; Kuemmeth, F.; Steele, G. A.; Grove-Rasmussen, K.; Nygård, J.; Flensberg, K.; Kouwenhoven, L. P. (Rev. Mod. Phys., 2015)